Pengaruh Pemakaian Kontrasepsi Oral,Suntik dan Implan Terhadap Keparahan Gingivitis(Tinjauan pada Aseptor KB di Puskesmas Kebonarum Kabupaten Klaten) - Kusumawati, Minda Saptari; , drg. Edi Karyadi, MM; , drg. S E Yuletnwati, MDSc (2016)
Contraception is a deterrent of the process of conception ovum by a sperm cell or the prevention of attachment of the ovum that had fertilized by sperm cell into the uterine wall. There are two types of contraceptives; hormonal and non-hormonal. The hormonal contraceptive is contraception that involves hormones in the process while non-hormonal does not involve any hormones. There are three ways in hormonal contraception, such as oral contraceptives containing estrogen and progesterone, injections and implants containing only progesterone. The variation of progesterone and estrogen in the contraceptives may affect the periodontal tissues, especially the increase of gingival inflammation. The aim of this study was to determine the effect of oral, injections, and implants contraceptives on the severity of gingivitis on the family planning acceptors in Puskesmas Kebonarum, Klaten Regency. The method used in this study was observational analytic by cross sectional approachment. The respondents of this study were 120 family planning acceptors aged 20-35 years in Puskesmas Kebonarum, Klaten Regency. The study was conducted in 27-31 May 2016. The sampling technique of this study was purposive sampling, in which, the respondents were asked about their contraceptive use and got explanation about the examination process. If they agreed to be respondent, they may sign the informed consent sheet. Then there was short counseling regarding dental and oral health related to the use of contraceptives. The examination in this study were Oral Hygiene Index (OHI) and gingival index (GI) in order to determine the gingivitis severity of the respondents. The result showed that there were 88 respondents with gingivitis. This study tested by using chi square test and obtained the value of p = 0.002 (p <0.05) to see the effect of oral, injections, and implants contraceptives on the severity of gingivitis. These data were analyzed by using SPSS 20.00 for windows. This study conclude that there was influence among users of oral contraceptives, injectable and implantable against the severity of gingivitis. Keywords: oral contraceptives, injectable contraceptives, contraceptive implants, severity of gingivitis.